Origin of Extremely Intense Southward Component of Magnetic Field (Bs) in ICMEs - Shen, Chenglong; Chi, Yutian; Xu, Mengjiao; Wang, Yuming (Frontiers in Physics, 2021)
The intensity of the southern component of the magnetic field (B_s) carried by Interplanetary Coronal Mass Ejections (ICMEs) is one of the most critical parameters in causing extreme space weather, such as intense geomagnetic storms. In this work, we investigate three typical ICME events with extremely intense B_s in detail and present a statistical analysis of origins of intense B_s in distinct types of ICMEs based on the ICME catalogue from 1995 to 2020. According to the in-situ characteristics, the ICME events with extremely high B_s are classified into three types: isolated ICMEs,multiple ICMEs, shock-ICME interaction events with shocks inside ICMEs, or shocks passed through ICMEs. By analyzing all ICME events with B_s 10nT and B_s 20nT, we find that the interaction events, particularly the shock-ICME interaction events have a greater chance of carrying extreme intense B_s. Only based on the in-situ observations at Earth, some interacting ICME events, such as shock-ICME interaction events with shocks passed through the preceding ICME or ICME cannibalism, could be classified as isolated ICME events. This may lead to an overestimation of the probability of ICME carrying extremely intense B_s. To further investigate such events, direct and multi-point observations of the CME propagation in the inner heliosphere from the Solar Ring Mission could be crucial.